On the absolute continuity of mappings distorting the moduli of cylinders - Salimov, R. R.; Sevost'yanov, E. A.; Салимов, Р. Р.; Севостьянов, Е. А.; Салимов, Р. Р.; Севостьянов, Е. А. (Institute of Mathematics, NAS of Ukraine, 2017)
We consider the mappings satisfying one modular inequality with respect to cylinders in the space. The distortion of modulus is majorized by an integral depending on a certain locally integrable function. We also prove a result on the absolute continuity of the analyzed mappings on lines.